1995
DOI: 10.1002/jrs.1250260103
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopic study of organ cultured corneae

Abstract: Raman spectroscopy of water was used to assess the metabolic state of fresh corneae and those which had been stored under long‐term organ culture conditions. Both human and porcine tissue were employed. The data showed a semi‐quantitative relationship between corneal hydration (determined using wet and dry weights of the tissue) and the integrated intensity of the water to collagen bands in the spectral region 2700—4000 cm−1. Variables included duration of storage, composition of culture medium and, for the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…The technique was utilized previously to study, e.g., protein and DNA conformations, drug interactions with bio-macromolecules and enzymes structure and action. 1,2 More recently it has been applied to determine the total water content in human organ-cultured corneas 3 and to characterize the ocular lens and its transformation from the normal to the cataractous state. 4 Using Raman spectroscopy, changes in the structural proteins and hydration state of the skin, hair and nail have recently been investigated by Gniadecka and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was utilized previously to study, e.g., protein and DNA conformations, drug interactions with bio-macromolecules and enzymes structure and action. 1,2 More recently it has been applied to determine the total water content in human organ-cultured corneas 3 and to characterize the ocular lens and its transformation from the normal to the cataractous state. 4 Using Raman spectroscopy, changes in the structural proteins and hydration state of the skin, hair and nail have recently been investigated by Gniadecka and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Bauer et al 29 found a decrease in corneal thickness of 50 µm in rabbit corneas exposed to an ambient environment after 30 min. Siew et al 37 detected an increase in hydration after excision and storage of human eye bank corneas in medium (corneal swelling). This work demonstrates the feasibility of real-time monitoring of the hydration changes in the living cornea, as illustrated by the OH/CH ratio versus time in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are monitoring the healing process following PRK; monitoring corneal grafts; monitoring hydration status of the cornea while exploring new laser wavelengths for refractive keratectomy; determining changes of corneal hydration after the use of topically applied drugs; 39 following the reaction of corneal tissue on contact lens usage; and quality control and selection of eye bank eyes. 37 Maximum and minimum swelling properties of the corneal stroma could be studied and how stress events such as contact lenses or a cataract extraction would interfere with these properties. 40 -42 It might be possible that the forced dehydration with Muro 128  can be applied as a test for endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…A micro-Raman spectroscopic study of organcultured corneas was performed by Siew et al [58] to investigate if quality control of these eye bank corneas was feasible using this technique. It proved to be a sensitive technique for measurements in a non-contact fashion.…”
Section: Cornea and Scleramentioning
confidence: 99%